2019
DOI: 10.1016/j.forpol.2019.101996
|View full text |Cite
|
Sign up to set email alerts
|

Rewilding forestry

Abstract: Rewilding has become highly popular amongst conservationists, ecologists, geographers and others, but interest is considerably less obvious amongst foresters. Whilst overall the amount of research focused on rewilding continues to grow rapidly, very few papers published within core forestry journals engage with the concept. In this commentary, we offer some potential explanations for this lack of engagement which include rewilding's early focus on animals (especially carnivores), its conceptual overlap with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Indeed, a lower FCI, together with lower canopy density, illustrates the lowland zones' poor conservation status regarding the interior areas. Higher FCI values found in the mountain belt suggest the progression towards the formation in mature closed forests, especially in protected areas, from where rewilding processes are underway due to the decrease of anthropogenic pressures (Dandy & Wynne‐Jones, 2019). These two different forest dynamics are also evident concerning the degraded forests in 1936.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a lower FCI, together with lower canopy density, illustrates the lowland zones' poor conservation status regarding the interior areas. Higher FCI values found in the mountain belt suggest the progression towards the formation in mature closed forests, especially in protected areas, from where rewilding processes are underway due to the decrease of anthropogenic pressures (Dandy & Wynne‐Jones, 2019). These two different forest dynamics are also evident concerning the degraded forests in 1936.…”
Section: Discussionmentioning
confidence: 99%
“…meat production that leads to deforestation (Jennings et al 2020). Moreover, it will be important to discuss the relationship between industrial forest management and degrowth, while alternative approaches to contemporary forestry, like rewilding, can inform this debate (Dandy and Wynne-Jones 2019). This also relates to the question of harvesting levels and forest reserves.…”
Section: A Degrowth View Of the Swiss Forest Sectormentioning
confidence: 99%
“…It has been suggested that a lack of clarity regarding the concept of rewilding (e.g. definitions, key principles) remains a barrier to rewilding application (Coźar-Escalante, 2019;Dandy and Wynne-Jones, 2019;Jones and Comfort, 2020). Some progress is being made towards consensus, as demonstrated by the IUCN CEM guiding principles and definition, which highlight social and ecological goals and implications for rewilding practice (Carver et al, 2021).…”
Section: Introductionmentioning
confidence: 99%